Impact of Different Land-Use Systems on Soil Physicochemical Properties and Macrofauna Abundance in the Humid Tropics of Cameroon - Lawrence Tatanah Nanganoa; Justin Nambangia Okolle; Valentine Missi; Jacques Roberto Tueche; Lewis Dopgima Levai; Jetro Nkengafac Njukeng (Applied and Environmental Soil Science)
The impact of different land-use systems on some soil physicochemical properties and macrofauna abundance in the humid tropics of Cameroon was studied. The land-use types included secondary forest (SF), oil palm plantation (PP), banana plantation (BP), sugarcane plantation (SP), and rubber plantation (RP). Soil particle size distribution, bulk density (BD), pH, organic matter (OM), and number of macrofauna were evaluated. The results showed that OM and number of macrofauna were higher in the SF than in the other land-use types. Pearson’s correlation analysis carried out to determine the relationship between OM and BD showed that OM and BD was strongly negatively related with correlation coefficient of −0.9653. It also showed a strong significant negative correlation between BD and ants population (r = −0.8828) and between soil pH and number of earthworms (r = −0.9072). Based on the results, the SF produced more organic matter and higher number of macrofauna. However, the OM of the other land uses was not low; hence, it could be beneficial to return plant residues to the field for maintaining soil quality.